2015
DOI: 10.1002/ijc.29600
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and mid‐life diet and subsequent risk of thyroid cancer in the NIH‐AARP diet and health study

Abstract: Although thyroid cancer is suspected to have a nutritional etiology, prospective studies examining the relationship between diet and thyroid cancer are lacking. During 1996–1997, NIH-AARP Diet and Health Study participants, ages 51–72 years, completed a 37-item food frequency questionnaire about diet at ages 12–13 years (adolescence) and 10 years before baseline (mid-life). Over a median 10 years of follow-up, 325 individuals (143 men and 182 women) were diagnosed with thyroid cancer. Multivariable-adjusted ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
2
10
1
1
Order By: Relevance
“…A meta‐analysis of 19 case‐control studies and a pooled‐analysis of 11 case‐control studies summarized the associations between vegetable intake and TC risk, showing a weak inverse association with the intake of total vegetables and vegetables excluding cruciferous vegetables. An American cohort study of 300,000 participants (the NIH‐AARP diet and health study) showed an impact of adolescent (12–13 years old) and midlife diet (10 years before recruitment when respondents were 41–62 years of age) on TC risk, with a significant inverse association of vegetable intake among women . Although intakes of vegetables consumed by both Americans at midlife and our study population were comparable, we did not find any association between the intake of vegetables and the risk of differentiated TC either overall or by subtype.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…A meta‐analysis of 19 case‐control studies and a pooled‐analysis of 11 case‐control studies summarized the associations between vegetable intake and TC risk, showing a weak inverse association with the intake of total vegetables and vegetables excluding cruciferous vegetables. An American cohort study of 300,000 participants (the NIH‐AARP diet and health study) showed an impact of adolescent (12–13 years old) and midlife diet (10 years before recruitment when respondents were 41–62 years of age) on TC risk, with a significant inverse association of vegetable intake among women . Although intakes of vegetables consumed by both Americans at midlife and our study population were comparable, we did not find any association between the intake of vegetables and the risk of differentiated TC either overall or by subtype.…”
Section: Discussionsupporting
confidence: 78%
“…Zamora-Ros et al Cancer Epidemiology respondents were 41-62 years of age) on TC risk, with a significant inverse association of vegetable intake among women. 27 Although intakes of vegetables consumed by both Americans at midlife and our study population were comparable, we did not find any association between the intake of vegetables and the risk of differentiated TC either overall or by subtype.…”
Section: Cancer Epidemiologycontrasting
confidence: 66%
See 2 more Smart Citations
“…Korde et al (30) further found that soy consumption in childhood, and all through life, was associated with a reduced risk of breast cancer. Diet during adolescence and midlife may be associated with risks of thyroid (31) and colorectal (27) cancer, with a reduced risk of colorectal cancer appearing to be associated with childhood milk consumption (23,32). Despite the evidence suggesting that early-life diet may influence risk of cancer later in life, to our knowledge there are no studies that have examined early-life diet in relation to pancreatic cancer.…”
mentioning
confidence: 98%